Role of high endothelial postcapillary venules and selected adhesion molecules in periodontal diseases: a review. (14th May 2012) - Kasprzak, A.; Surdacka, A.; Tomczak, M.; Konkol, M.
<x xml:space="preserve">Abstract</x> Periodontitis is accompanied by the proliferation of small blood vessels in the gingival lamina propria. Specialized postcapillary venules, termed periodontal high endothelial‐like venules, are also present, and demonstrate morphological and functional traits similar to those of high endothelial venules (HEVs) in lymphatic organs. The suggested role of HEVs in the pathogenesis of chronic periodontitis involves participation in leukocyte transendothelial migration and therefore proinflammatory effects appear. Recent observations suggest that chronic periodontitis is an independent risk factor for systemic vascular disease and may result in stimulation of the synthesis of acute phase protein by cytokines released by periodontal high endothelial cells (HECs). However, tissue expression of HEV‐linked adhesion molecules has not been evaluated in the gingiva of patients with chronic periodontitis. This is significant in relation to potential therapy targeting expression of the adhesion molecules. In this review, current knowledge of HEV structure and the related expression of four surface adhesion molecules of HECs [CD34, platelet endothelial cell adhesion molecule 1, endoglin and intercellular adhesion molecule 1 (ICAM‐1)], involved in the key steps of the adhesion cascade in periodontal diseases, are discussed. Most studies on the expression of adhesion molecules in the development and progression of periodontal diseases pertain to ICAM‐1 (CD54). Studies by the authors demonstrated quantitatively similar expression of three of four selected surface markers in gingival HEVs of patients with chronic periodontitis and in HEVs of reactive lymph nodes, confirming morphological and functional similarity of HEVs in pathologically altered tissues with those in lymphoid tissues.